PROSES MEMBANGUN PENGETAHUAN KONSEPTUAL PADA SISWA KELAS VIII DALAM PEMBELAJARAN MATEMATIKA DI SMP NEGERI 1 KUDUS - Arisjanti, Nova Ayu; Sujadi, Imam; Kusmayadi, Tri Atmojo (Journal of Mathematics and Mathematics Education, 2014)
Abstract: The objective of this research is to describe the process of conceptual knowledge building of the students in Grade VIII in Mathematics learning at State Junior High School 1 of Kudus. This research used a qualitative case study method. The subjects of the research were three students in Grade VIII of the school with the high, medium, and low academic abilities respectively. The subjects of the research were chosen by using the purposive sampling technique. The data of the research were gathered through passive participatory observations. All of the learning activities were documented by taping them with handy camera. Based on data analysis of the three students in Grade VIII with the high, medium, and low academic abilities respectively in mathematics learning at the cube and cuboid elements at State Junior High School 1 of Kudus are as follows. (1) The process of conceptual knowledge building of the subject of the research with the low academic ability. Initially the knowledge associated with submitted materials teachers are still global. The information and knowledge obtained from doing the exercises, through: (a) visualizing the shape of cube and cuboid into the other shape to identify the elements; (b) making the relation and category classification between cube and cuboid. Doing the other activity, like: (a) learning the note book, handbook, and studentâs work sheet; (b) using the complete note book as reference in the learning; (c) attending courses. (2) The process of conceptual knowledge building of the subject of the research with the medium academic ability. Initially knowledge obtained from teacher in the mathematics learning still global. The information and knowledge obtained from doing the exercises, through: (a) making the relation and category classification between cube and cuboid; (b) identifying the side of shape from cuboid through example. Doing the other activity, like: (a) relearning the material; (b) using material from explanation the teacher as reference in the learning; (c) giving certain signs if there are differences in the contents of the learning materials of the books learned; (d) doing the different exercises with example from the teacher; (e) attending courses. (3) The process of conceptual knowledge building of the subject of the research with the high academic ability. Initially acquired knowledge not as detailed as what the teachers explained. The information and knowledge obtained from doing the exercises, through: (a) discussion; (b) visualizing the shape of cube and cuboid into the other shape to indentify the elements; (c) determining criteria of classification the cube and cuboid. Doing the other activity, like: (a) reading the material; (b) doing the exercises from the formula and solution in the handbook; (c) attending courses.Keywords: the process of knowledge building, conceptual knowledge, and mathematics learning.